Singapore fashion industry. - Ng, Siow Hui. (2008)
The overview of local fashion industry, interviewing local designers and also, to find out more about the business development locally and overseas. In addition, by analyzing the consumers' survey results, we obtain consumers' attitudes and their awareness level of the local brands. Thereafter, we present recommendations to the industry and conclusions of research.